Black sun : a novel - Matthews, Owen (Doubleday, 2019)
"A chilling and cinematic thriller set in 1961 in one of the most secretive locations in Soviet history. Ten days before the test of largest nuclear device in history--the Tsar Bomba--a KGB officer must investigate the murder of one of the architects of the bomb, and unravel a conspiracy that could set the world on fire"--